Inclusive Leadership and Its Effect on Employee Performance Outcomes - Thabo Mbeki; Sipho Dlamini; Nomvula Zuma (PT. Sangadji Media Publishing, 2025)
Inclusive leadership has gained increasing attention as organizations seek leadership approaches that foster both equity and performance in diverse work environments. This study examines the effect of inclusive leadership on employee performance outcomes using a quantitative research design. Data were collected through a cross-sectional survey of 287 full-time employees working in medium to large organizations. Inclusive leadership was measured using a validated scale capturing leaders’ openness, accessibility, and availability, while employee performance outcomes were assessed through task and contextual performance indicators. The data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis. The results reveal a positive and statistically significant relationship between inclusive leadership and employee performance outcomes. Inclusive leadership was found to be a strong predictor of employee performance after controlling for demographic variables, explaining a substantial proportion of variance in performance outcomes. These findings support social exchange theory and social identity theory by demonstrating that inclusive leadership behaviors encourage employees to reciprocate with higher levels of performance and organizational contribution. The study contributes to the leadership and human resource management literature by providing empirical evidence on the performance-enhancing role of inclusive leadership within a highly diverse organizational context. Practically, the findings highlight the importance of integrating inclusive leadership principles into leadership development and human resource practices to enhance employee performance and organizational effectiveness.